Remembering LKY : the crafting of the LKY narrative - Chang, En En (2019)
During Lee Kuan Yew’s (‘Lee’) death in 2015, an unexpected phenomenon occurred – the worship of Lee. Alongside this worship, Lee experienced the elevation of his status, magnification of his contributions, and widespread perpetuation of him to the younger generations. In this essay, it is argued that the apparent worship observed in 2015 could not have possibly been produced solely from the overwhelming grief or crowd psychology experienced. Rather, it was the culmination of the repeated elements within the Singapore Story that had overlapped and intertwined with Lee’s history and experiences. This repetition of the elements marking the Singapore story began when Lee’s just won the first election and took office in 1965. The two entities continued to intertwine unti l his death, where it peaked and caused the widespread proliferation of Lee’s narrative. This essay will use the framework by Charlotte Linde in the way institutions, in this case the government who is seen as synonymous to Lee, uses narratives to remember and shape its members (Singaporeans) identity.